Lossless integration of multiple electronic health records for identifying pleiotropy using summary statistics - Ruowang Li (Nature Portfolio, 2021)
Thus far, pleiotropy analysis using individual-level Electronic Health Records data has been limited to data from one site. Here, the authors introduce Sum-Share, a method designed to efficiently and losslessly integrate EHR and genetic data from multiple sites to perform pleiotropy analysis.